MIDIATIZAÇÃO E CIRCULAÇÃO DE SENTIDOS NAS MANIFESTAÇÕES DE JUNHO DE 2013 - Bezerra, Patrícia Rangel Moreira (2015)
The communication systems have seen significant changes since the arrival of the internet, where participatory devices grow every day, due to the increasingly more evident process of a mediated society. This paper addresses the issue of June manifestations occurring in Brazil, tries to reveal the tensions of the mainstream media discourse against alternative media coverage reflects what were the consequences of a major manifestation that the country has seen and analyzes the movement of felt in the events of 2013. Therefore, combines a bibliographical and historical research with empirical research focused on the analysis of narratives of Arnaldo Jabor columns journalist for Radio CBN, during the demonstrations, as well as two comments on video Jabor, to Jornal da Globo, TV Globo. And to highlight the theoretical framework of this study, we analyzed a third video, which is entitled La Hipocresia de los Medios, due to the issue of the Bajada de Línea program, the TV Argentina, which echoes the lines of Arnaldo Jabor, becomes literally a third speech, showing the change of opinion and confirming that the media coverage affects the classical model of communication.